Pengaruh latihan SKJ 2018 terhadap kebugaran jasmani siswi Madrasah Aliyah Ja-alHaq di Kota Bengkulu - Lismana, Oetari; Suwarni, Suwarni (UNIVED Press, Universitas Dehasen Bengkulu, 2021)
THE EFFECT OF SKJ 2018 EXERCISES ON FITNESS PHYSICAL OF MADRASAH ALIYAH JA-ALHAQ FEMALE STUDENTS IN BENGKULU CITY By: Oetari Lismana Student Reg. ID: 17190079 Thesis of S1 Physical Education Study Program The University of Dehasen Bengkulu, 2021: 141 Pages This study aims to determine the effect of SKJ 2018 exercises on improving the physical fitness of students at Madrasah Aliyah Ja-alHaq in Bengkulu City. In this study using the method of Preexperimental Design with One Group Pretest-Posttest Design, it can be noted with certainty the difference in results due to the treatment given. The population in this study were students who took extracurricular activities at Madrasah Aliyah Ja-alHaq in Bengkulu City as many as 30 people and the research sample used total sampling, namely the sampling technique by taking all members of the population as respondents or a sample of 30 people. The statistical analysis used in this study was the t-test to test the hypothesis that there is an effect of the 2018 SKJ exercise on improving the physical fitness of the students of Madrasah Aliyah Ja-alHaq in Bengkulu City. The results of the t test calculation analysis turned out to have a significant effect on the results of physical fitness. The calculation results state that the final test with the calculation of the value of tcount 8,758 > ttable 1,699 with a level of = 0.05 means that there is a significant effect between X (SKJ 2018 exercises) and Y (physical fitness improvement) with an increase of 9.1% Based on the results of hypothesis testing that has been carried out, it is stated that there is a significant effect between the SKJ 2018 exercises on improving the physical fitness of Madrasah Aliyah Ja-alHaq students in Bengkulu City. Keywords: SKJ 2018 Exercises, Physical Fitness Improvement